GAMBARAN PENGETAHUAN DAN PERILAKU MASYARAKAT MENGENAI PHBS RUMAH TANGGA PADA PENYAKIT DIARE DI KELURAHAN KEDAMIN HULU KECAMATAN PUTUSSIBAU SELATAN - Lia Okta Wahyuni; Malik Saepudin; Moh. Adib (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Pontianak, 2022)
Diarrhea is one of the environmental-based infectious diseases which is still an important health problem when viewed from the morbidity and mortality rates in Indonesia. The causes of diarrheal disease are increasing, among others, due to the lack of public knowledge about clean and healthy living behavior which of course has an impact on public health. This type of research is an observational study with a descriptive approach, which describes the level of knowledge and behavior of the community regarding clean and healthy living behavior and diarrheal diseases in Kedamin Hulu urban village, South Putussibau sub-district. The data obtained are presented in the form of a frequency distribution table. The results of this study indicate the level of knowledge in the good category (46%), moderate (30%), less (24%). Clean and healthy behavior (46%), not clean and healthy behavior (54%). Respondents who experienced diarrhea (55%), who were not sick (45%). The level of public knowledge about clean and healthy living behavior is good but in the behavior of daily life, people have not implemented clean and healthy living behavior so there are still some cases of diarrheal disease caused by clean and healthy living behavior that has not been implemented properly.